Vascular Calcification in Chronic Kidney Disease: The Role of Vitamin K- Dependent Matrix Gla Protein - Roumeliotis, Stefanos; Dounousi, Evangelia; Salmas, Marios; Eleftheriadis, Theodoros; Liakopoulos, Vassilios (Frontiers in Medicine, 2020)
Arterial calcification is highly prevalent in chronic kidney disease (CKD) patients and is associated with cardiovascular (CV) morbidity and mortality. Patients at early CKD stages are more likely to suffer a fatal CV event than to develop end-stage renal disease and require hemodialysis treatment. The heavy CV burden of these patients cannot be solely explained by traditional calcification risk factors. Moreover, the pathophysiologic mechanisms underlying this association are complex and yet not fully understood. Although vascular calcification was regarded as a passive degenerative process for over a century, this theory changed by recent evidence that pointed towards an active process, where calcification promoters and inhibitors were involved. Matrix Gla Protein (MGP) has been established as a strong inhibitor of calcification both in vitro and in vivo. Not only it prevents mineralization of the arterial wall, but it is the only factor that can actually reverse it. To become fully active, MGP must undergo carboxylation of specific protein bound glutamate residues, a process fully dependent on the availability of vitamin K. Low vitamin K status leads to inactive, uncarboxylated forms of MGP and has been repeatedly associated with accelerated vascular calcification. Aim of this review is to present the pathophysiologic mechanisms underlying the activation and function of MGP and review the existing, accumulating data regarding the association between vitamin K, MGP and vascular calcification/CV disease in CKD patients.